Studying the Nature of Human Factor and Developing the Method of Solving the Problem - L. Marinov, Marin; Vasil'evich Osipchuk, Igor'; Aleksandrovna Malygina, Elena (International Journal of Engineering and Technology, 2018)
The studies of human influence on the effectiveness of professional activity should consider that the concept of â€œhuman factorâ€ is too general, and it is impossible to use it for an objective evaluation of humanâ€™s professional activity. The most powerful and robust factors of human behavior, such as virtue, will and interest, are not considered enough in the studies of the influence of the human factor on the individualâ€™s professional activity.The research results presented in the article change the existing opinion that the only way to increase the effectiveness of professional activity is to increase the effort to select people with the necessary qualities, skills and high level of professional and psychological training. Such effort to optimize the secondary factors, and ignorance towards the effect of the key behavioral factors (virtue â€“ will â€“ interest), are the fundamental errors and the reasons of the low work effectiveness.Â Â Â